Association between the temperature difference and acute exacerbations of chronic obstructive pulmonary disease: A time-series analysis with 143,318 hospital admissions in Beijing, China - Fu, Jia; Liu, Yanbo; Zhao, Yakun; Chen, Yuxiong; Chang, Zhenge; Xu, Kai-Feng; Huang, Cheng; Fan, Zhongjie (Frontiers in Public Health, 2023)
(1) Purpose: AECOPD has the adverse influence on quality-of-life and creates significant healthcare costs. However, there were sparse studies investigating the correlation between AECOPD hospital admissions and temperature change. Therefore, it is noteworthy to investigate the impact of various temperature differences and recognize the susceptible population. The purpose of this study was to investigate the impact of temperature differences on AECOPD hospital admissions, as well as to give potentially helpful material for disease preventative efforts. (2) Methods: The distributed lag non-linear model was adopted to characterize the exposure-response relationship and to assess the impact of temperature difference. The stratified analysis and sensitivity analysis were also conducted to determine the susceptible populations and examine the robustness of the results. (3) Results: There were 143318 AECOPD hospital admissions overall during the study period. The AECOPD hospital admissions had significant association with the extreme-cold temperature difference (1st DTDmean), the ultra-cold temperature difference (5th DTDmean), the ultra-hot temperature difference(95th DTDmean) and the extreme-hot temperature difference (99th DTDmean) and there was the “U-shaped” association between DTDmean and 21 days cumulative relative risk of AECOPD. (4) Conclusion: The AECOPD hospital admissions was correlated with the DTDmean temperature differences, especially the extreme-cold and extreme-hot temperature difference. Moreover, people older than 65 years were more susceptible to the extreme-hot and extreme-cold temperature difference.